Eksistensi Peradilan In Absentia Dalam Kasus Tindak Pidana Korupsi Oleh Angkatan Bersenjata di Pengadilan Militer - Shira Casta Aurellia; Irwan Triadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Purpose of this writing is to determine the existence of in absentia trials in military law, especially in trying cases of criminal acts of corruption involving the armed forces in military courts. The existence of trials in absentia, in military courts, is a complex and controversial legal issue. Trial in absentia refers to a trial conducted without the presence of the defendant in the trial process in the courtroom. In military criminal law, this trial is only regulated for the crime of desertion. This then raises ethical debates regarding how to apply trial in absentia in cases of other criminal acts. In cases where military members are involved in criminal acts of corruption, military courts play a crucial role. On the other hand, trial in absentia can be considered to maintain the continuity of the legal process in order to achieve legal certainty, especially when the defendant deliberately flees from the judicial process. The existence of in absentia trials in military courts in cases of criminal acts of corruption by the armed forces is not specifically regulated in its application, however, the judicial process in corruption cases is regulated according to the rules in Law Number 31 of 1997 concerning Military Courts and Law Number 46 of 2009 concerning Courts Specifically for Corruption Crimes. The judicial process will continue to run according to the law that regulates it in order to achieve justice and legal certainty.